There is a Crack in Everything: Biblical Texts Questioning the Legitimation of Violence in the Name of the One God - Spronk, Klaas (Exchange, 2016)
As a contribution to the ongoing discussion about the relation between monotheism and violence a comparison is made between polytheistic stories about the annihilation of mankind and the monotheistic Old Testament story of the flood. There appear to be many ambiguities in Genesis 6-9, also concerning the image of God. This leaves room for criticism on the abuse of power. Whereas polytheism tends to fatalism, monotheism seems to offer a more hopeful view. It cannot be denied, however, that the Old Testament also testifies of monotheism which does not tolerate deviating religious views and in this way can be used to legitimize violence. Nevertheless, there are small but important indications in the text describing violence in the name of God that God is broader minded in this regard than many religious hardliners see Him. Inspired by a text of Leonard Cohen one could call them ‘cracks’ in the holy scriptures which will help to let more light of tolerance come in.